Comparison of Glucose Administration Routes to Determine Glucose Tolerance in Old and Young Mice (Baltic Journal of Sport and Health Sciences, 2022)
Background: It has been observed that old mice have a better tolerance to glucose than young after an intraperitoneal injection of glucose. We hypothesized that an intraperitoneal injection of glucose overestimates glucose tolerance in old mice.Methods: We assessed differences in glucose tolerance outcomes in 2- (young, n=23) and 23- to 27-month-old (old, n=23) male C57BL/6J mice after an intraperitoneal (IP) or intravenous (IV) injection, or oral gavage (OG) of glucose.Results: The area under the curve (AUC) of the changes of blood glucose concentration over 2 hours after glucose administration was lower in old than young animals (p